2008
DOI: 10.1128/jvi.00116-08
|View full text |Cite
|
Sign up to set email alerts
|

Histone Hyperacetylation Occurs on Promoters of Lytic Cycle Regulatory Genes in Epstein-Barr Virus-Infected Cell Lines Which Are Refractory to Disruption of Latency by Histone Deacetylase Inhibitors

Abstract: Activation of the Epstein-Barr virus (EBV) lytic cycle is mediated through the combined actions of ZEBRA and Rta, the products of the viral BZLF1 and BRLF1 genes. During latency, these two genes are tightly repressed. Histone deacetylase inhibitors (HDACi) can activate viral lytic gene expression. Therefore, a widely held hypothesis is that Zp and Rp, the promoters for BZLF1 and BRLF1, are repressed by chromatin and that hyperacetylation of histone tails, by allowing the access of positively acting factors, le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
110
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(113 citation statements)
references
References 84 publications
3
110
0
Order By: Relevance
“…Recently, studies of these histone marks in specific promoter regions in the EBV genome have yielded some interesting results from an analysis of the epigenetic patterns of viral genes, such as Cp, LMP2A and BZLF1, which code for essential latent proteins. As these histone marks are associated with open and accessible chromatin, these results suggested that, in coordination with DNA methylation, they have a major role in the modulation (activation or repression) of specific viral genes (Gerle et al, 2007;Countryman et al, 2008;Fejer et al, 2008).…”
Section: Epstein-barr Virusmentioning
confidence: 94%
See 2 more Smart Citations
“…Recently, studies of these histone marks in specific promoter regions in the EBV genome have yielded some interesting results from an analysis of the epigenetic patterns of viral genes, such as Cp, LMP2A and BZLF1, which code for essential latent proteins. As these histone marks are associated with open and accessible chromatin, these results suggested that, in coordination with DNA methylation, they have a major role in the modulation (activation or repression) of specific viral genes (Gerle et al, 2007;Countryman et al, 2008;Fejer et al, 2008).…”
Section: Epstein-barr Virusmentioning
confidence: 94%
“…This reactivation is initiated by the expression of the immediate-early gene BZLF1, which encodes the transcriptional activator Zta, probably by stimuli such as plasma cell differentiation, and has been found to be unmethylated (Fernandez et al, 2009). This protein, apart from affecting the expression of host genes (Chang et al, 2006), has the ability to bind to methylated sites and activate the expression of BRLF1, another of this virus's immediate-early genes, and both together then activate the expression of the remaining lytic genes, thereby inducing a lytic infection (Bhende et al, 2005;Countryman et al, 2008;Dickerson et al, 2009;Heather et al, 2009). …”
Section: Epstein-barr Virusmentioning
confidence: 99%
See 1 more Smart Citation
“…As a first step, we used the TPA ĂŸ NaB combination as the most commonly used treatment to trigger EBV lytic reactivation (2,21). Healthy donor-derived LCLs treated for 48 hours with TPA ĂŸ NaB showed significantly increased BARF1 mRNA expression (2.5 mean fold-increase, P 0.05; Fig.…”
Section: Doxorubicin Upregulates Barf1 Mrna Expressionmentioning
confidence: 99%
“…Changes in histone acetylation in the BZLF1 promoter region results in activation of BZLF1 gene expression leading to reactivation from latency, as treatment with histone deacetylase (HDAC) inhibitors can activate viral lytic gene expression (7)(8)(9). It is reported that, in latently infected cells, the silent state of the virus genome is maintained, at least in part, by MEF2-mediated recruitment of HDAC proteins to the BZLF1 promoter region (10).…”
mentioning
confidence: 99%